IMPLEMENTATION OF ECOTOURISM IN THE MANAGEMENT OF CANDIREJO HERBAL KAMPUNG SURABAYA - Sucipto Sucipto (Universitas Terbuka, 2019)
Ecotourism is a tourism activity that balances between utilization and saving (conservation). And one of the goals of the principle of ecotourism is to improve the economy of local communities. Candirejo Herbal Kampung Surabaya is one of the villages in Surabaya that promotes